Struktura izbranih spremenljivk tekmovalne uspešnosti smučarjev skakalcev na ZOI v Pekingu 2022 na večji skakalnici - Jošt, Bojan (Šport (Ljubljana), 2022)
The research study aimed to establish the relation between selected variables and competitive performance of ski jumpers who competed in the first series on the big ski jump at the 2022 Beijing Winter Olympics. In this competition the International Ski Federation introduced measurement of ski jumpers’ take-off velocity at the 30-metre point from the edge of the take-off ramp. The angle between the skis was also measured at this point. Ski jumpers’ velocity at the landing was measured completely anew. Competitive performance was statistically significantly related to the variables of run-up velocity (r=0.32; p=0.05) and flight velocity before landing (r=0.44; p=0.01). The influence of wind velocity was not present in this Olympic competition. Judges’ scores did not affect the ranking of the best competitors who won Olympic medals. It was impossible to largely explain competitive performance using a small number of independent variables, which is why new questions keep emerging about the structure of factors that influence ski jumpers’ competitive performance. Slovenian male and female ski jumpers were the most successful participants of the Olympics in ski jumping. To stay on top of competitive performance means constantly looking for new creative and effective training methods and means which are mainly based on knowledge and high-quality practical work.
Keywords: olimpijske igre; Peking 2022; skakalci; smučarski skoki; šport; športna tekmovanja; tekmovalna uspešnost